2018
DOI: 10.1080/13651501.2018.1426771
|View full text |Cite
|
Sign up to set email alerts
|

Challenging predictions between affective temperaments, depression and anxiety in a Kosovo student community sample

Abstract: Study findings are consistent with some other studies and stress the importance of screening for effective temperament in order to early identify depression and anxiety. Further investigation is needed to understand what are other factors that influence the relationship between affective temperaments with depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
3
0
1
Order By: Relevance
“…Moreover, the Kesebir study showed that people diagnosed with depression score lower in the TEMPS-A regarding hyperthymic temperament ( 10 ). The above data are compatible with the Shahini study, which also revealed a negative correlation between a hyperthymic temperament and depressive symptoms and a positive correlation between depression and the previously mentioned temperament types ( 20 ). According to a study conducted on subjects from the general population in Hungary, the Zung Self-Rating Depression Scale (ZSDS) score was assessed with TEMPS-A results; anxious, depressive, and cyclothymic temperaments were in substantial positive correlation with depressive scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the Kesebir study showed that people diagnosed with depression score lower in the TEMPS-A regarding hyperthymic temperament ( 10 ). The above data are compatible with the Shahini study, which also revealed a negative correlation between a hyperthymic temperament and depressive symptoms and a positive correlation between depression and the previously mentioned temperament types ( 20 ). According to a study conducted on subjects from the general population in Hungary, the Zung Self-Rating Depression Scale (ZSDS) score was assessed with TEMPS-A results; anxious, depressive, and cyclothymic temperaments were in substantial positive correlation with depressive scores.…”
Section: Discussionsupporting
confidence: 92%
“…These increased the risk of affective disorders, including depression ( 17 ). On the other hand, there is speculation that a hyperthymic temperament can provide resistance to depression ( 20 ). The prognosis and course of depression could also be affected by one’s temperament ( 15 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Das ermöglicht gemeinsam mit der bereits erlernten prospektiven Life-Chart [1,9,10] eine lückenlose Erfassung des Verlaufes [2,11] und seiner Determinanten [12][13][14][15][16][17] durch die bipolare Person. Manche Aspekte des Moduls V (Verlauf) werden durch das Ausfüllen der retrospektiven Life-Chart am eigenen Beispiel deutlich, etwa die Bedeutung von Mischzuständen [18,19], von Komorbiditä-ten [20][21][22][23][24][25][26][27], von Polaritätswechseln [28,29], von Therapieresistenz [29][30][31] und des Verlaufstyps [32,33]. Dieses stellt eine große Hilfe für den therapeutischen Prozess dar -auch in Hinblick auf das Erreichen von Adhärenz [34] und einer gutenpsychosozialenFunktionsfähigkeit [35] -und macht die Patientin/den Patienten zur Expertin/zum Experten ihrer/ seiner Erkrankung.…”
Section: Informationen Zu Bipolaren Störungen Und Darstellungen In Film Und Literaturunclassified
“…So far, research results show that utilization of TEMPS-A may provide interesting data regarding the evaluation of patients’ predisposition to depression and anxiety or in determining the diagnosis of bipolar disorders. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%